Labor Market Effects of Immigration – Evidence from Neighborhood Data - Thomas K. Bauer; Regina Flake; Mathias G. Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This paper combines individual-level data from the German Socio-Economic Panel (SOEP) with economic and demographic postcode-level data from administrative records to analyze the effects of immigration on wages and unemployment probabilities of high- and low-skilled natives. Employing an instrumental variable strategy and utilizing the variation in the population share of foreigners across regions and time, we find no support for the hypothesis of adverse labor market effects of immigration. – – In diesem Papier werden Individualdaten des Sozio-Ökonomischen Panels (SOEP) mit ökonomischen und demographischen Informationen auf Postleitzahlebene aus administrativen Daten verknüpft, um den Effekt von Zuwanderung auf Löhne und die Wahrscheinlichkeit von Arbeitslosigkeit von niedrig- und hochqualifizierten Einheimischen zu analysieren. Unter Verwendung eines Instrumentvariablenansatzes und unter Ausnutzung der regionalen und zeitlichen Variation des Anteils von Ausländern in der Bevölkerung unterstützen unsere Ergebnisse nicht die Hypothese, dass Zuwanderung negative Auswirkungen auf den Arbeitsmarkterfolg von Einheimischen hat.
Keywords: F22; J31; J64; R23; 330; International migration; effects of immigration; Einwanderung; Migranten; Regionaler Arbeitsmarkt; Qualifikation; Lohn; Arbeitslosigkeit; Schätzung; Deutschland